Selection of hematopoietic stem cell transplantation for T-cell lymphoblastic lymphoma - Li, Zhen; Zhang, Binglei; Fan, Xinxin; Gui, Ruirui; Yu, Fengkuan; Wang, Juan; Zhang, Yanli; Zhou, Keshu; Liu, Yanyan; Li, Yufu; Ding, Jing; Song, Yongping; et al. (Frontiers in Oncology, 2023)
Background: Hematopoietic stem cell transplantation (HSCT) is an important treatment for T-cell lymphoblastic lymphoma/leukemia (T-LBL). To compare the efficacy and influencing factors of autologous hematopoietic stem cell transplantation (auto-HSCT) with those of allogeneic hematopoietic stem cell transplantation (allo-HSCT) from different donors for the treatment of T-cell lymphoblastic lymphoma/leukemia (T-LBL) and provide a basis for selection of appropriate transplant methods and donors. Methods: To provide evidence of appropriate transplant methods for these patients, we retrospectively summarized the clinical characteristics of 75 T-LBL patients receiving HSCT at Henan Cancer Hospital between March 2012 and October 2021. Overall survival (OS), progression-free survival (PFS), cumulative incidence of relapse (CIR), non-relapse mortality (NRM), and related factors affecting efficacy were analyzed.Results: The 3-year CIR (39.9% vs 31.1%, P=0.745), 3-year PFS (60.1% vs 49.6%, P=0.434), and 3-year OS (62.8% vs 53.0%, P=0.450) were not significantly different between the auto-HSCT and allo-HSCT groups. However, the 3-year NRM was significantly higher in the allo-HSCT group (0% vs 27.2%, P=0.033). Multivariate analysis showed that the first complete remission (CR1) after HSCT was an independent influencing factor of higher OS (HR=2.498, P=0.029) and PFS (HR=2.576, P=0.016). The absence of mediastinal invasion in patients receiving HSCT was an independent influencing factor of better PFS (HR=2.977, P=0.029) and lower CIR (HR=4.040, P=0.027). With respect to the impact of donor source, the NRM in the unrelated donor (URD) and haploid donor (HPD) groups was significantly higher than that in the auto-HSCT group (P=0.021 and P=0.003, respectively), while there was no significant difference between matched sibling donors (MSD) and auto-HSCT.Compared with the MSD-HSCT group, the auto-HSCT group showed an increasing trend in 3-year CIR (39.9±11.1% vs 32.6±11.2%, P=0.697) and a lower trend in 3-year OS (62.8±11.4% vs 64.4±12.2%, P=0.929).Conclusions: HSCT is an effective consolidation treatment option for patients with T-LBL without mediastinal invasion and with CR1 before transplantation. For CR1 patients, auto-HSCT and MSD-HSCT are effective modalities for improving survival. In non-CR1 patients without an MSD, matched unrelated donors and haploidentical donor transplantations are the best treatment options to reduce relapse and improve prognosis.